Coexistence of ribbon and helical fibrils originating from hIAPP(20-29) revealed by quantitative nanomechanical atomic force microscopy - Zhang, Shuai; Andreasen, Maria; Nielsen, Jakob T; Liu, Lei; Nielsen, Erik H; Song, Jie; Ji, Gang; Sun, Fei; Skrydstrup, Troels; Besenbacher, Flemming; Nielsen, Niels C; Otzen, Daniel E; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Uncontrolled misfolding of proteins leading to the formation of amyloid deposits is associated with more than 40 types of diseases, such as neurodegenerative diseases and type-2 diabetes. These irreversible amyloid fibrils typically assemble in distinct stages. Transitions among the various intermediate stages are the subject of many studies but are not yet fully elucidated. Here, we combine high-resolution atomic force microscopy and quantitative nanomechanical mapping to determine the self-assembled structures of the decapeptide hIAPP(20-29), which is considered to be the fibrillating core fragment of the human islet amyloid polypeptide (hIAPP) involved in type-2 diabetes. We successfully follow the evolution of hIAPP(20-29) nanostructures over time, calculate the average thickening speed of small ribbon-like structures, and provide evidence of the coexistence of ribbon and helical fibrils, highlighting a key step within the self-assembly model. In addition, the mutations of individual side chains of wide-type hIAPP(20-29) shift this balance and destabilize the helical fibrils sufficiently relative to the twisted ribbons to lead to their complete elimination. We combine atomic force microscopy structures, mechanical properties, and solid-state NMR structural information to build a molecular model containing β sheets in cross-β motifs as the basis of self-assembled amyloids.